2021
DOI: 10.1088/1755-1315/934/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

EEL (Anguilla bicolor bicolor) Rearing Techniques at the UPTD for Conservation and Supervision of Marine Fishery Resources of Sicincin, West Sumatra

Abstract: Eel has a savory meaty taste and contains high levels of Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA). The purpose of this observation was to determine intensive rearing techniques for eel (Anguilla bicolor bicolor) at the UPTD KPSDKP for Conservation and Supervision of Marine Fishery Resources of Sicincin, West Sumatra. The preparations conducted for rearing the eel consist of providing seeds, pond preparation, water supply, feed management, water quality control, disease control, growth samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The results of temperature measurements at each station showed that the temperature ranged from 29-31°C. This is in accordance with the statement of [13] which states that the optimal temperature for the life of mud crabs is in the range of 25-35 °C. The results of salinity measurements at each station obtained salinity results ranging from 20-25‰.…”
Section: Water Quality Parameter Measurementsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of temperature measurements at each station showed that the temperature ranged from 29-31°C. This is in accordance with the statement of [13] which states that the optimal temperature for the life of mud crabs is in the range of 25-35 °C. The results of salinity measurements at each station obtained salinity results ranging from 20-25‰.…”
Section: Water Quality Parameter Measurementsupporting
confidence: 92%
“…The results of salinity measurements at each station obtained salinity results ranging from 20-25‰. This is in accordance with the statement of [13] which states that a good salinity for the life of mud crabs is 10-25‰. The pH measurement value at each station showed that the pH ranged from 7-8.…”
Section: Water Quality Parameter Measurementsupporting
confidence: 88%
See 1 more Smart Citation